The effect of x-ray radiation on malondialdehyde levels in radiology workers in selected hospitals in Indonesia - Ardyanto W, Y Denny; Tualeka, Abdul Rohim; Rachman, Rizaldy Fathur; Thamaraikani, Tamilanban; Perumal, Velu; Ahsan, Ahsan; Rahmawati, Pudji; Zurimi, Suardi; Novianti, Salsabila (Politeknik Kesehatan Kementerian Kesehatan Surabaya, 2024)
The use of ionizing radiation in radiology units is essential for disease diagnosis. However, this radiation has enough energy to ionize atoms and molecules in the material it passes through, potentially posing health risks. This study aimed to analyze the effect of an effective dose of X-ray radiation on malondialdehyde (MDA) levels, a marker of oxidative stress, in radiographers. With an observational design, this study was conducted cross-sectionally at hospitals X and Y from January to April 2023, involving 19 radiographers exposed to X-ray radiation. MDA levels were measured using the Thio Barbituric Acid Reactive Substances (TBARS) method, and data were analyzed using SPSS, including descriptive, bivariate, and multivariate analyses. The results showed that all respondents had abnormal MDA levels, but the effective radiation dose did not significantly affect MDA levels (p > 0.05). In contrast, working hours significantly influenced MDA levels, where an increase in working hours correlated with an increase in MDA levels. Thus, although the radiation dose is considered safe, there is evidence of significant oxidative stress in radiographers, which requires further attention regarding managing radiation exposure in the work environment.